Ellie Pillai is brown - Pillainayagam, Christine (Ellie Pillai, 2022)
My name is Ellie. Ellie Pillai... And I suppose I am a little bit weird, but then, aren't we all, just a little bit? Ellie Pillai has no idea how to apply eyeliner properly, or what makes people cool. She just hears songs in her head and sees dancing girl groups, which is a bit well... weird. Most of the time, Ellie feels completely invisible -- and usually she's ok with that. But not this year. Maybe it's the new boy at school who makes her brain explode into rainbows every time she sees him (and also happens to be the boyfriend of her very best friend), or maybe it's her new drama teacher, the one who seems to have noticed she exists. Or maybe, just maybe, it's the lie she told, that feels like it's about to blow up her life... Suddenly, Ellie's misfit style, her songwriting and all that getting lost in the music in her head mean everyone is watching. But maybe standing out isn't a bad thing after all?